Successfully Treating an Odontogenic Keratocyst with Surgery and Carnoy’s Solution: A Case Study: Berhasil Mengobati Keratokista Odontogenik dengan Pembedahan dan Solusi Carnoy: Sebuah Kasus Studi - Al_Sheikhly , Athraa A. Ahmed (Indonesian Journal on Health Science and Medicine, 2025)
Odontogenic keratocyst (OKC) is a type of cyst found in the jaw that has sparked debate on whether it should be classified as a cyst or a tumor. While it was briefly categorized as a tumor (KCOT) due to its aggressive behavior and unique microscopic appearance, it has since been reclassified as a cyst in the latest World Health Organization guidelines. (1) This study presents the case of an 18-year-old male who underwent successful surgical removal of a large OKC in his lower jaw. The procedure involved carefully removing the cyst, trimming surrounding bone, and applying a solution to minimize recurrence. After six months, the patient showed no signs of the cyst returning. This case highlights the effectiveness of a conservative surgical approach in treating OKC, leading to minimal complications, quick healing, and restored jaw function Highlights: Classification: OKC is reclassified as a cyst by WHO guidelines. Case: Successful surgical removal of OKC in an 18-year-old male. Outcome: Conservative surgery ensured minimal complications and no recurrence after six months Keywords: Bone Cysts. Odontogenic keratocyst. Enucleation. Bone healing.